Effect of Spray Tips and Mix Deposition on Common Water Hyacinth Growing with Varied Population Arrangements of Salvinia and Water Lettuce - De Marchi, Sidnei Roberto (2009)
Water hyacinth (Eichhornia crassipes) and other free floating plants continue to cause significant management problems in Brazilian reservoirs constructed for power generation. Herbicide management for control of these free-floating plants is currently under evaluation. In this study we evaluated two types of spray tips (ConeJet TXVK-8 and TeeJet DG 11002 VS) and the amount of spray mix deposited onto water hyacinth (Eichhornia crassipes) plants organized in different population arrangements with eared watermoss (Salvinia auriculata) and water lettuce (Pistia stratiotes) plants. In addition to a 100% water hyacinth arrangement, we tested arrangements with either eared watermoss or water lettuce at 75:25%, 50:50%, and 25:75%, plus a triple density with the three species placed equally at a 33% proportion. Dye solutions of FDC Yellow No. 5 at 3500 ppm and FDC Blue No. 1 at 1000 ppm were used as spraying tracers for TXVK-8 and DG 11002 VS nozzles, respectively. Both solutions were sprayed on the same plot at 30-min intervals through a CO(2) pressured backpack knapsack calibrated to deliver a spray volume around 200 L/ha. The TXVK-8 tip provided greater spray mix deposition when compared to the DG 11002VS tip, regardless of the plant proportions. For both spray tips, higher proportions of eared watermoss and the triple association among the plants provided the highest spray mix deposition on water hyacinth plants. The increase of spray mix deposition is likely related to the increase of eared watermoss or water lettuce as well as the decrease of water hyacinth plants in the association and consequent decreases of self covering among water hyacinth leaves. Lake managers should consider that improved herbicide uptake is possible through the choice of nozzle as well as applying herbicides to hyacinth before it forms dense monocultures or dense mixtures with other free-floating plants.